Digital Text and Brazilian Folklore: Discussion on Referential Activity and Beyond - Figueira-Cardoso, Samuel (2023)
This paper discusses how socio-communicative practices that originate in oral tradition, with a focus on Brazilian legends, manifest themselves in the digital environment. It foregrounds the production of discourse objects as a category of analysis and approaches the theoretical assumptions of linguistic and cultural studies through an interdisciplinary approach. It is a study of a theoretical-analytical nature that aims to answer the following research questions: How are Brazilian folk narratives constructed in multimodal texts-based interactions in digital environment? How are the objects of discourse constructed in the analyzed texts? The analyzed texts were collected through screenshots of interactions on public Facebook pages. It is hoped that the results will allow us to understand how digital texts are constructed and show how referential processes contribute to text construction and meaning production, deepening studies of language use in digital environments.
Keywords: digital text; folk narratives; referencing; linguistic analysis; meaning making